Spooks in the machine. (Economist, 2024)
The article reports on the accusations by Western countries like the U.S., Great Britain and New Zealand against China's alleged major cyber-espionage campaign and their efforts to address it. Also cited are the sanctions imposed by the British and American governments against the Chinese hacking group APT31 and the claim by U.S. Federal Bureau of Investigation (FBI) head Christopher Wray that Chinese hackers are preparing the groundwork for a possible attack on U.S. infrastructure.